2023
DOI: 10.3389/fcell.2023.1113046
|View full text |Cite
|
Sign up to set email alerts
|

Transposon-derived transcription factors across metazoans

Abstract: Transposable elements (TE) could serve as sources of new transcription factors (TFs) in plants and some other model species, but such evidence is lacking for most animal lineages. Here, we discovered multiple independent co-options of TEs to generate 788 TFs across Metazoa, including all early-branching animal lineages. Six of ten superfamilies of DNA transposon-derived conserved TF families (ZBED, CENPB, FHY3, HTH-Psq, THAP, and FLYWCH) were identified across nine phyla encompassing the entire metazoan phylog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
0
2
0
1
Order By: Relevance
“…A good example of this is the expansion in proteins with the FLYWCH domains identified in M. rasmusseni . A recent analysis of DNA transposon-derived transcription factors in animals found that FLYWCH-domain containing transcription factors are rare in animals but have undergone expansion in one phylum of non-bilaterian animals – Ctenophora (Mukherjee & Moroz, 2023). This study did not include myxozoans in their comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…A good example of this is the expansion in proteins with the FLYWCH domains identified in M. rasmusseni . A recent analysis of DNA transposon-derived transcription factors in animals found that FLYWCH-domain containing transcription factors are rare in animals but have undergone expansion in one phylum of non-bilaterian animals – Ctenophora (Mukherjee & Moroz, 2023). This study did not include myxozoans in their comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the myriad detrimental effects that TEs have on the genome, they also have positive effects and their regulatory sequences have been co-opted by a number of genes (71, 72). In addition, numerous genes have arisen through ‘domestication’ of TEs, including proteins involved in the function of the brain and placenta (72), as well as a large number of transcription factors (73). They can also act as drivers of gene duplication, even after they have lost the ability to transpose on their own (72).…”
Section: Discussionmentioning
confidence: 99%
“…В геномах животных среди ТЕ доминируют короткие неавтономные ретротранспозоны, у растений -эндогенные ретровирусы (54); у животных, по крайней мере позвоночных, ключевым элементом в архитектонике интерфазного ядра, по-видимому, служит мотив посадки TF CTCF, у растений -сложный комплекс мотивов, вовлекаемых в межбелковые взаимодействия (77). Существенно различаются и семейства ТЕ, последовательности которых составляют основу для формирования факторов регуляции транскрипции TF у многоклеточных (78). Один из ярких примеров участия TE в приобретении новых признаков у животных -формирование и эволюция плаценты млекопитающих, связанные с активностью эндогенных ретровирусов, многие семейства которых были одомашнены с последующей генерацией новых регуляторных генов или регуляторных элементов (79).…”
Section: рис 4 размер генома эукариот и доля некодирующей аминокислот...unclassified